Mouse 2.0: Multi-touch meets the mouse - Villar, Nicolas; Izadi, Shahram; Rosenfeld, Dan; Benko, Hrvoje; Helmes, John; Westhues, Jonathan; Hodges, Steve; Ofek, Eyal; Butler, Alex; Cao, Xiang; Chen, Billy (Proceedings of UIST 2009, ACM Symposium on User Interface Software and Technology, 2009)
In this paper we present novel input devices that combine the standard capabilities of a computer mouse with multi-touch sensing. Our goal is to enrich traditional pointer-based desktop interactions with touch and gestures. To chart the design space, we present five different multi-touch mouse implementations. Each explores a different touch sensing strategy, which leads to differing form-factors and hence interactive possibilities. In addition to the detailed description of hardware and software implementations of our prototypes, we discuss the relative strengths, limitations and affordances of these novel input devices as informed by the results of a preliminary user study.